How Environmental Leadership Promote Technological Innovation in Resource-Based Enterprises: The Role of Green Investment and Government Subsidy - Xiuming Sun; Xuan Ding; Min Zheng; Lin Liu; Hanqi Yu (IEEE Access)
Technological innovation represents the core driving force for the green development of resource-based enterprises. How to effectively promote enterprises’ technological innovation has received considerable attention in academia and practice. However, most of existing studies have been focused on the influence of industrial level or organizational level, the impact of leadership has received little attention. Therefore, this study explores the impact of environmental leadership, which focuses on environmental protection and sustainable development, on technological innovation. Using Stata 18 software, this study analyzes 170 resource-based enterprises listed on the Shenzhen and Shanghai A-share stock markets, for the time periods spanning from 2013 to 2022. The results indicate a positive impact of environmental leadership on technological innovation, with green investment mediating the relationship between environmental leadership and technological innovation. However, the moderating effect of government subsidies between environmental leadership and green investment is not significant. Our findings offer a better understanding of technological innovation in resource-based enterprises by considering the influence factors from both internal and external pespectives, especially the critical role of leader. Therefore, this study contributes to the literature on leadership theory and technological innovation theory.